Population genetic characteristics and mating type frequency of Venturia effusa from Pecan in South America - Bock, Clive H.; Frusso, Enrique Alberto; Zoppolo, Roberto; Ortiz, Edson R.; Shiller, Jason; Charlton, Nikki D.; Young, Carolyn; Randall, Jennifer J. (American Phytopathological Society, 2024)
Scab, caused by the plant-pathogenic fungus Venturia effusa, is a major disease of pecan in South America, resulting in loss of quantity and quality of nut yield. Characteristics of the populations of V. effusa in South America are unknown. We used microsatellites to describe the genetic diversity and population structure of V. effusa in South America, and determined the mating type status of the pathogen. The four hierarchically sampled orchard populations from Argentina (AR), Brazil (BRC and BRS), and Uruguay (UR) had moderate to high genotypic and gene diversity. There was evidence of population differentiation (Fst = 0.196) but the correlation between geographic distance and genetic distance was not statistically significant. Genetic differentiation was minimal between the UR, BRC, and BRS populations, and these populations were more clearly differentiated from the AR population. The MAT1-1 and MAT1-2 mating types occurred in all four orchards and their frequencies did not deviate from the 1:1 ratio expected under random mating; however, multilocus linkage equilibrium was rejected in three of the four populations. The population genetics of South American populations of V. effusa has many similarities to the population genetics of V. effusa previously described in the United States. Characterizing the populations genetics and reproductive systems of V. effusa are important to establish the evolutionary potential of the pathogen and, thus, its adaptability—and can provide a basis for informed approaches to utilizing available host resistance and determining phytosanitary needs.